FREQUENCY OF ESOPHAGEAL FOREIGN BODIES AND THEIR SITE OF IMPACTION IN PATIENTS PRESENTING WITH FOREIGN BODY AERODIGESTIVE TRACT - Raza Muhammad; Zakir Khan; Aisha jamil; Sohail Malik; Tahir Haroon; Farida Khan; Rehman Ghani (European Scientific Journal, ESJ, 2013)
Background: One third of foreign bodies retained in the gastrointestinal tract are present in the esophagus. Their management depends on the anatomic location, shape and size of the foreign body and duration of impactionObjective: To determine the frequency, their site of impaction and method of removal of esophageal foreign bodies among patients reporting with aero digestive tract foreign body.Material and MethodsThis was a Descriptive study conducted at the ENT Department, Ayub Medical Institute (AMI) Abbottabad from June 2011 to June 2012. A total of 100 patients were included in the study presenting with foreign body ingestion that underwent esophagoscopy under general anesthesia. The type and site of impaction of foreign body and method of removal was noted.Results: A total of 100 patients were included with age ranging from 1 to 90 years and the mean age was 14.60 ± 21.13 years. Among the patients with foreign body in aero digestive tract, the foreign body in esophagus was noted in 57% patients. The most common foreign body was coin (56%). The foreign bodies were seen most commonly among children of age 1 – 5 years (55%). Rigid endoscopy was most common procedure performed to remove the foreign body (84%).Conclusion: Esophageal foreign bodies are most commonly seen among patients with foreign body in aero digestive tract. Coins are the most common type. Rigid endoscopy is most commonly performed procedure to remove them.